THE ROLE OF THE LAWYER IN A PLEA AGREEMENT. (World Bulletin of Management and Law, 2024)
The article describes the concept of the participation of a lawyer in the conduct of criminal cases of a separate category, in particular, in the Proceedings of cases in which an agreement on a confession of guilt is concluded, its characteristics, significance
Keywords: defender; lawyer; settlement